Strategi Meningkatkan Keterampilan Berpikir Kritis melalui Penggunaan Model Problem Based Learning - Herlinawati, Mike; Hidayat, Sholeh; Jamaludin, Ujang; Yandari, Indhira Asih Vivi (Paedagogie, 2025)
This study aims to describe how teachers' strategies improve critical thinking skills by implementing a problem-based learning model. This study uses a descriptive qualitative research method with data collection techniques through interviews, observation, and documentation. 21st-century education requires students to master not only knowledge but also skills. One of the skills in 21st-century learning that needs to be mastered and improved is critical thinking skills. The problem-based learning model is a learning model in which students are faced with a problem that aims to enable students to actively participate in learning. The results of this study indicate that there is an increase in students' critical thinking skills after participating in problem-based learning. This can be seen when students participate in learning, students are actively involved in discussions, ask questions, respect friends' opinions, and convey the results of their discussions.